2018
DOI: 10.3390/ijms19020324
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proteins Involved in Carbohydrate Metabolism and Energy Metabolism Pathways and Their Regulation of Cytoplasmic Male Sterility in Wheat

Abstract: Cytoplasmic male sterility (CMS) where no functional pollen is produced has important roles in wheat breeding. The anther is a unique organ for male gametogenesis and its abnormal development can cause male sterility. However, the mechanisms and regulatory networks related to plant male sterility are poorly understood. In this study, we conducted comparative analyses using isobaric tags for relative and absolute quantification (iTRAQ) of the pollen proteins in a CMS line and its wheat maintainer. Differentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 56 publications
(64 reference statements)
0
22
1
Order By: Relevance
“…The mitochondrial electron transfer chain, which is a major site for ROS production, is located in the mitochondrial membrane and catalyses the transfer high-energy electrons from NADH/FADH to adjacent complexes [31]. Many studies have shown that when electron transfer is reduced, excess electrons directly combine with molecular oxygen to produce excess ROS [32,33]. In the present study, the expression levels of cytochrome-c oxidase (Complex IV) were lower from the tetrad stage to the dinuclear stage in 722HA (Cluster 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial electron transfer chain, which is a major site for ROS production, is located in the mitochondrial membrane and catalyses the transfer high-energy electrons from NADH/FADH to adjacent complexes [31]. Many studies have shown that when electron transfer is reduced, excess electrons directly combine with molecular oxygen to produce excess ROS [32,33]. In the present study, the expression levels of cytochrome-c oxidase (Complex IV) were lower from the tetrad stage to the dinuclear stage in 722HA (Cluster 1).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that mitochondria encoded subunits of the F 1 F 0 -ATPase are associated with male sterility in plants [36,37]. In wheat CMS line KTM3315A, downregulated expression of the genes whose products encode F 1 F 0 -ATPase slows down the electron transfer rate, and excess electrons combine with molecular oxygen to form ROS, thus initiating PCD in the anthers [33]. In the present study, K-means cluster analysis of DEGs revealed that the expression levels of these genes in 722HA were significantly lower from the tetrad stage to the dinuclear stage (Cluster 1).…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose-phosphate synthase (SPS) is the key enzyme of sucrose synthesis, which is strongly linked to plant growth, photosynthesis characteristics, and fruit ripening (Ma et al, 2020). 6-Phosphofructokinase (PFK) is a key catalytic enzyme involved in fructose phosphorylation and plays an important role in fructose metabolism (Geng et al, 2018). PFK is also a key enzyme in the glycolysis pathway and a rate-limiting enzyme.…”
Section: Dna Methylation Regulates Flowering Through Its Involvement In Carbon Metabolismmentioning
confidence: 99%
“…The expression of five ATP synthase-related genes (which encode mitochondrial proton-transporting ATP synthase complex and coupling factor F0) with important functions in ROS generation [36,37] decreased in the order of P9B, P9BS, and P9SA. Ubiquinol-cytochrome-c reductase (complex III, Unigene12642_All) and two cytochrome-c oxidase genes (complex IV, CL7398.Contig6_All, CL7398.Contig5_All), which cause electrons to bind directly to oxygen molecules and produce an excess of ROS [38,39], had the highest expression in P9B, the second highest expression in P9BS, and the lowest expression in P9SA in our study (Table S5).…”
Section: Degs Related To Rosmentioning
confidence: 68%